Governance of IKN development and its impact on investor confidence - Caecilia Cindy Aurelia; Prof. Dr. Dra. Dwi Windyastuti Budi Hendrarti, M.A.; Nuke Faridha Wardhani, S.IP., M.M. (Universitas Negeri Yogyakarta, 2025)
The development of the Archipelago's National Capital City (IKN) in East Kalimantan is expected to trigger national economic equality. However, until early 2024, the project has experienced significant delays, raising doubts among domestic and foreign investors. This study analyses how development stagnation affects investor confidence, particularly regarding risk perception, governance, and project sustainability. Using a case study and document-based qualitative approach, the research identified legal uncertainty, political risk, weak transparency, and socio-environmental issues as the main barriers to investment. Although the government offers various fiscal incentives, the majority of investors are still waiting because they consider the risks too high. The results of this study emphasise the importance of governance reform, inclusive policy communication, and compliance with sustainability (ESG) standards to restore confidence and attract long-term investment. The findings are expected to provide theoretical contributions on the concept of strategic investor confidence and practical recommendations for policymakers in the management of large-scale infrastructure projects in Indonesia.